Feasibility Study of Problem-Based Blended Learning Models to Improve Literacy - Lulud Prijambodo Ario Nugroho (Universitas Sebelas Maret, 2022)
One of the learning models is the problem-based learning model, which is then implemented in a blended manner. The feasibility study aimed to observe that the developed model could improve students' literacy skills. The feasibility study was conducted at a junior high school in Semarang Regency in February for approximately three weeks. Meanwhile, the number of respondents observed was 20 students in the eighth grade.There were two main factors in the observation of the picking test: the first was the social interaction of students in groups, and the second was the interaction of students with learning resources. On the other hand, the third factor was the impact of the interaction, i.e., the product or group solution.To facilitate observation, one class was divided into several groups, each consisting of up to five people. The results revealed relatively significant results because each group could develop learning resources to solve the problems through google search, then give good results, and solve the problems presented by the teacher.